Design and Implementation of Student and Alumni Web Portal - Sabri, Shaimaa Q.; Ahmad, Akeela M.; Abdulrazaq, Maiwan B. (Science Journal of University of Zakho, 2017)
The Information and Communication Technology (ICT) has witnessed great development in the recent years. Therefore, the design of Students and Alumni Web Portal (SAWP) involves the analysis of the internal and external environment of the three universities. For this آ آ purpose, SWOT technique has been used to detect the deep effect of environment factors on the strategic plan to discover the strengths, weaknesses, opportunities and threats facing the design of the proposed system. SAWP was designed using (MySQL, HTML, CSS, Java Script, jQuery, PHP, AJAX) techniques to provide robust portal system addressing two subsystems: student and alumni portal system. Testing of the SAWP was administered through two main stages: the first, to identify the studentâ€™s views and their preferences. The second to measure the usability of the system through using System Usability Scale (SUS) method with subscription of 22 potential آ آ system users. The best results of SUS testing are: the rate of overall satisfaction was high nearly 80%. While the implementation outcomes found very compatibility and reasonable in wide extents between available data and system requirements.